Simbiotik Negara dan Agama: Menelaah Relasi Hukum Sekuler dan Moralitas Keagamaan di Indonesia - Purwanto, Edi; Silalahi, Frans H. M. (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2025)
This article explores the relationship between secular law and religious morality within Indonesia’s legal system, which is built upon a symbiotic principle between the state and religion. Unlike strictly secular or theocratic states, Indonesia adopts a unique approach by integrating religious values into its legal framework through the ideological foundation of Pancasila and the constitutional mandate of the 1945 Constitution. This study employs a qualitative method with a literature review approach, focusing on Scopus-indexed publications and analyzed through content analysis techniques. The findings reveal that while Indonesia’s legal system normatively guarantees religious freedom, in practice, it still encounters challenges such as intolerance, the politicization of religion, discrimination against minority groups, and conflict among coexisting legal systems. The article concludes that the relationship between the state and religion in Indonesia requires structural and cultural reinforcement to achieve substantive justice and uphold the protection of diversity in a democratic society. This study contributes conceptually to the discourse on law and religion and offers practical implications for Christian education and the development of tolerant, justice-oriented citizens